Development of Magnetic Sponges Using Steel Melting on 3D Carbonized Spongin Scaffolds Under Extreme Biomimetics Conditions - Bartosz Leśniewski; Martin Kopani; Anna Szczurek; Michał Matczak; Janusz Dubowik; Martyna Kotula; Anita Kubiak; Dmitry Tsurkan; Eliza Romańczuk-Ruszuk; Marek Nowicki; Krzysztof Nowacki; Iaroslav Petrenko; et al. (Biomimetics, 2025)
This study presents a novel approach to fabricating magnetic sponge-like composites by melting various types of steel onto three-dimensional (3D) carbonized spongin scaffolds under extreme biomimetic conditions. Spongin, a renewable marine biopolymer with high thermal stability, was carbonized at 1200 °C to form a turbostratic graphite matrix capable of withstanding the high-temperature steel melting process (1450–1600 °C). The interaction between molten steel vapors and the carbonized scaffolds resulted in the formation of nanostructured iron oxide (primarily hematite) coatings, which impart magnetic properties to the resulting composites. Detailed characterization using SEM-EDX, HRTEM, FT-IR, and XRD confirmed the homogeneous distribution of iron oxides on and within the carbonized fibrous matrix. Electrochemical measurements further demonstrated the electrocatalytic potential of the composite, particularly the sample modified with stainless steel 316L—for the hydrogen evolution reaction (HER), offering promising perspectives for green hydrogen production. This work highlights the potential of extreme biomimetics to create functional, scalable, and sustainable materials for applications in catalysis, environmental remediation, and energy technologies.